Canadian Cinema in the Era of Globalization - Armatage, Kay (situArte, 1970)
In this article I will approach many of the currently dominant topics in relation to Canadian cinema: the impact on national cinemas and auteurism of international film festivals, shifts in distribution patterns, labour issues, production output, and globalised aesthetics, as well as other related issues, such as slippages in notions of populism and popularity. Also, I analyze the marks of globalization that are present in the Canadian film industry in the coproduction treaties and financing exigencies, as well as they are in other countries. I base my research in the postulates of Hjort (2010), Iordanova (2010), Chow (1995) and Hansen (2010) among others. Global cinema becomes increasingly drive n by genre, costly technologies, expertise, enormous budgets and superstars, but to trespass borders formerly marginal national cinemas may nevertheless transcend borders, cultures and ethnicities through dissemination via alternative channels, including the internet, film festivals, Iphone apps among others.